Kandungan Senyawa Fitokimia dan Aktivitas Antibakteri Ekstrak Daun Pepaya (Carica Papaya L.): Narrative Review - Umniyah Tsabitah Zahrani; Ihsanti Dwi Rahayu; Atri Sri Ulandari; Ramadhan Triyandi (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
This narrative review article explores the potential of papaya leaves (Carica papaya L.) as an alternative antibacterial treatment due to the increasing problem of antibiotic resistance. Papaya leaves, commonly found in Indonesia, are known to have various pharmacological properties, including antibacterial effects. The article aims to collect and review existing literature on the phytochemical compounds and antibacterial activity of papaya leaf extract. Literature searches were conducted across several databases such as Google Scholar, NCBI, ResearchGate, and ScienceDirect using keywords like